Experimental study on preparation and properties of low content rubberized geopolymer mortar. (17th October 2022) - Kuang, Fenglan; Long, Zhilin; Kuang, Dumin; Guo, Ruiqi; Sun, Jinlei
Highlights: Different blending ratios of raw materials have a great influence on the properties of geopolymer. Effects of rubber particle size on the working and mechanical properties of RGRM has been studied. Long term high temperature curing will reduce the compressive and flexural strength of RGRM. The morphology of rubber particles in RGRM is characterized by XRD and SEM. The developed rubber geopolymer repair mortar has good economic and environmental evaluation. Abstract: With the continuous increase of infrastructure construction, the supply of river sand is becoming increasingly scarce in recent years. Partially replacing river sand with waste rubber as fine aggregate has attracted extensive attention. Many studies were involved in the physical and mechanical properties of rubber mixed in ordinary mortar. However, there are few studies on the property changes of rubber blended into geopolymer mortar. In this study, a new type of rubberized geopolymer mortar (RGM) using rubber as fine aggregate replacement of 5 % river sand was investigated. Four kinds of rubber particle sizes are 4 mm, 1.7 mm, 0.83 mm and 0.27 mm respectively. The fluidity, compressive strength, flexural strength and microstructure of these RGMs were tested and analyzed in detail. Results show that the addition of rubber particles slightly reduces the fluidity of the corresponding geopolymer mortar (i.e., 22.4 cm), the fluidity of studied RGMs are within 17.6–21.5 cm. The compressive and flexural strength of RGMs also decrease with an increase of rubber particle size. However, RGMs have relatively high early strength, and their highest 1-d compressive and flexural strength can reach 47.2 MPa and 7.2 MPa, as well as 51.3 MPa and 8.2 MPa, respectively, at curing temperatures of 25 °C and 80 °C, implying that high-temperature curing can improve their early strengths. It is also found that the compressive and flexural strength of RGMs decline when these RGMs are cured at relatively high temperature for a long time.